The Correlation between Self-Regulated Learning and Motivation to The Achievement of PAI and Budi Pekerti at SMPN 2 Kediri - Qurrotul A'yun (Didaktika Religia, 2017)
This research is the result of quantitative research with multiple correlation design, aiming to test the theory from D.H. Schunk and B.J. Zimmerman that Self-regulated learning is generally characterized as an active participant who efficiently controls their own learning experiences in different ways, and answers questions about how much self-regulated learning, motivation, and learning outcomes of PAI and Budi Pekerti of students SMPN 2 Kediri, and there is correlation between self-regulated learning and motivation to the learning outcomes of PAI and Budi pekerti at SMPN 2 Kediri. Data collection techniques in this study are documentation and questionnaires of self-regulated learning and motivation. While the analysis technique is kendall's tau. The results of this study show, first of all, that self-regulated learning is categorized as very high; second, motivation is categorized high; third, PAI and Budi Pekerti learning outcomes are categorized as high based on score criteria; fourth, there is a significant relationship between self-regulated learning and motivation to the learning outcomes of PAI and Budi Pekerti at SMPN 2 Kediri.